Potensi Green Economy Dalam Mendukung Tujuan Pembangunan Berkelanjutan Pada Pabrik Beras Bintang Nipah Emas Di Tinjau Dari Ekonomi Syariah - Ahmad Syukron Prasaja; Dessy Anggraini; Andika Andika (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
. Nowadays global problems whose impact on the environment are no stranger to human life. A clean and beautiful environment will have a positive impact on human health and vision, however, this phenomenon is very rare or even more difficult to find. So researchers are interested in conducting research at a rice factory in the Nipah Panjang II area. The rice factory is a factory that processes paddy into rice. The researcher intends to apply the green economy concept to the factory in the hope of reducing the losses caused by the factory to the surrounding environment and supporting the goals of sustainable development. The research method used in this research is a qualitative research method and uses descriptive research. Meanwhile, the data sources used in this research are primary data and secondary data, while the data collection techniques used are observation, interviews, questionnaires and documentation. It is known that the research results obtained in this research are that the factory carries out a rice milling process using a machine that is fueled by ethanol and the waste produced is re-managed into something that can be useful and generate additional income for the factory